Distinct patterns of innate immune activation by clinical isolates of respiratory syncytial virus. - Ruth Levitz; Yajing Gao; Igor Dozmorov; Ran Song; Edward K Wakeland; Jeffrey S Kahn (PLoS ONE, 2017)
Respiratory syncytial virus (RSV) is a major respiratory pathogen of infants and young children. Multiple strains of both subgroup A and B viruses circulate during each seasonal epidemic. Genetic heterogeneity among RSV genomes, in large part due to the error prone RNA-dependent, RNA polymerase, could mediate variations in pathogenicity. We evaluated clinical strains of RSV for their ability to induce the innate immune response. Subgroup B viruses were used to infect human pulmonary epithelial cells (A549) and primary monocyte-derived human macrophages (MDM) from a variety of donors. Secretions of IL-6 and CCL5 (RANTES) from infected cells were measured following infection. Host and viral transcriptome expression were assessed using RNA-SEQ technology and the genomic sequences of several clinical isolates were determined. There were dramatic differences in the induction of IL-6 and CCL5 in both A549 cells and MDM infected with a variety of clinical isolates of RSV. Transcriptome analyses revealed that the pattern of innate immune activation in MDM was virus-specific and host-specific. Specifically, viruses that induced high levels of secreted IL-6 and CCL5 tended to induce cellular innate immune pathways whereas viruses that induced relatively low level of IL-6 or CCL5 did not induce or suppressed innate immune gene expression. Activation of the host innate immune response mapped to variations in the RSV G gene and the M2-1 gene. Viral transcriptome data indicated that there was a gradient of transcription across the RSV genome though in some strains, RSV G was the expressed in the highest amounts at late times post-infection. Clinical strains of RSV differ in cytokine/chemokine induction and in induction and suppression of host genes expression suggesting that these viruses may have inherent differences in virulence potential. Identification of the genetic elements responsible for these differences may lead to novel approaches to antiviral agents and vaccines.